Subacute thyroiditis following COVID-19 vaccination: Case presentation - Tomic, Aleksandra Z; Zafirovic, Sonja S; Gluvic, Zoran M; Samardzic, Vladimir S; Macvanin, Mirjana T; Radunovic, Maja LJ; Isenovic, Esma R (Antiviral therapy, 2023)
Background: Subacute thyroiditis (SAT) is an organ-specific disease that various drugs, including COVID-19 vaccines, can trigger. COVID-19 infection has been associated with thyroid gland damage and disease SARS-CoV-2 direct action, euthyroid sick syndrome, and immune-mediated mechanisms are all potential mechanisms of thyroid damage. It denotes thyroid gland inflammation, most commonly of viral origin, and belongs to the transitory, self-limiting thyroid gland diseases group, causing complications in approximately 15% of patients in the form of permanent hypothyroidism. Some authors say SAT is the most common thyroid disease associated with COVID-19. Purpose: The occurrence of SAT many weeks after administering the second COVID-19 vaccine is rare and has limited documentation in academic literature. This study aims to present the occurrence of SAT after administering the COVID-19 vaccine. We present the case of a 37-year-old man who developed SAT 23 days after receiving the second dose of Pfizer BioNTech's COVID-19 mRNA vaccine. Research design and study sample: Due to neck pain and an elevated body temperature (up to 38.2°C), a 37-year-old male subject presented for examination 23 days after receiving the second Pfizer BioNTech mRNA vaccine against SARS-CoV-2 viral infection. The patient denied ever having an autoimmune disease or any other disease. Painful neck palpation and a firm, slightly enlarged thyroid gland with no surrounding lymphadenopathy were identified during the exam. The heart rate was 104 beats per minute. All of the remaining physical findings were normal. Data collection and/or Analysis: Data collected during the disease are integral to the medical record. Results: Hematology and biochemistry analyses at the initial and follow-up visits revealed minor leukocytosis, normocytic anaemia, and thrombocytosis, followed by a mild increase in lactate dehydrogenase and decreased iron levels. The patient's thyroid function and morphology had recovered entirely from post-vaccine SAT. Conclusions: Results from this study emphasise the need for healthcare professionals to promptly report any case of SAT related to COVID-19 vaccination. Further investigation is warranted to understand the immunopathogenesis of COVID-19-associated thyroiditis and the impact of COVID-19 immunization on this condition.